Characteristics of the plasmid-mediated colistin-resistance gene mcr-1 in Escherichia coli isolated from a veterinary hospital in Shanghai - Lin, Hongguang; Chen, Wenxin; Zhou, Rushun; Yang, Jie; Wu, Yong; Zheng, Jiaomei; Fei, Shuyue; Wu, Guiting; Sun, Zhiliang; Li, Jiyun; Chen, Xiaojun (Frontiers in Microbiology, 2022)
The mobile colistin-resistance (mcr)-1 gene is primarily detected in Enterobacteriaceae species, such as Escherichia coli and Salmonella enterica, and represents a significant public health threat. Herein, we investigated the prevalence and characteristics of mcr-1-positive E. coli (MCRPEC) in hospitalized companion animals in a pet hospital in Shanghai, China, from May 2021 to July 2021. Seventy-nine non-duplicate samples were collected from the feces (n = 52) and wounds (n = 20) of cats and dogs and the surrounding hospital environment (n = 7). Seven MCRPEC strains, identified using screening assays and polymerase chain reaction, exhibited multidrug-resistant phenotypes in broth-microdilution and agar-dilution assays. Based in whole-genome sequencing and bioinformatics analyses, all seven isolates were determined to belong to sequence type (ST) 117. Moreover, the Incl2 plasmid was prevalent in these MCRPEC isolates, and the genetic environment of the seven E. coli strains was highly similar to that of E. coli SZ02 isolated from human blood. The isolates also harbored the β-lactamase gene blaCTX-M-65, and florfenicol resistance gene floR, among other resistance genes. Given that horizontal transfer occurred in all seven strains, E. coli plasmid transferability may accelerate the emergence of multidrug-resistant bacteria and may be transmitted from companion animals to humans. Therefore, the surveillance of MCRPEC isolates among companion animals should be strengthened.